China and Climate Multilateralism: A Review of Theoretical Approaches - Zhang, Hao (2022)
China’s approach to multilateral climate negotiation has shifted greatly over the past decades. From being an obstacle to a follower, and now a potential leader, China has attracted academic attention. This article surveys the literature on China’s role in climate multilateralism as examined by scholars through different lenses. The article asks whether analyses at different policymaking levels can explain China’s changing position. I review studies addressing the international level and the nexus between the complementary international and domestic levels to offer a comprehensive understanding of China’s strategic moves and choices in multilateral discussions on climate change. The review finds that factors at the international level are influencing China’s climate ambitions and goals, and even to some extent are determining its strategies toward climate multilateralism; however, for China to deliver its international climate commitments, its enhanced ability will need domestic support. While these insights are valuable to understand China’s international behavior, an emerging framework needs to be included in this discussion, as transnational governance scholarship might be able to explain how new actors may unlock China’s position on climate change in the future.